Kitāb al-mulakhkhaṣ fi ʼl-lugha maʿa ʼl-wafāʾ bi-tarjamat mā fi ʼl-Qurʾān - Jaʿfarī-Dihaqī, Maḥmūd (Miras Maktoob, ISBN: 9789004365452., 2019)
A trusted and much-used means to navigate between words and languages, the dictionary has a long history. The oldest bilingual dictionary is a Sumerian-Eblaite lexicon of more than 4000 years ago. The earliest monolingual dictionary is preserved in fragments from a Chinese lexicon from around 800 BCE. As for Arabic-Persian dictionaries, of which the facsimile published here is a valuable specimen, these made their first appearance in the 4th/10th century, at the time of the first translations of the Qurʾān and its commentaries and the increase of scientific texts in Arabic eligible for translation into New Persian. The present dictionary was copied in 684/1286, but is certainly older than that. It is a general lexicon which has been alphabetically arranged. At the end there is an appendix with an overview of the terminology of various practical fields that leaves a very modern impression (days of the week, basic arithmetic etc.). Historical and philological introducton, indices.